PENGARUH FAKTOR PSIKOLOGIS KONSUMEN SEBAGAI PENDORONG KEPUTUSAN PEMBELIAN ONLINE - Rena Feri Wijayanti; Tri Yulistyawati Evelina; Lina Budiarti; Joni Dwi Pribadi (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2023)
The research's purpose is to examine the effect of consumers' psychological factors consist of motivation, perception, learning, beliefs, and attitudes toward online purchase decisions. This research focuses on Gen Z in the Malang Raya that have made purchases through the marketplace especially Shopee which is not deeply studied yet on previous research. The sample of this research is 97 respondents by purposive sampling. Data analysis has conducted by multiple linear regression. Finding of this research is a phycological factor has a significant effect on online purchase decisions.